Una mirada interpretativa y constitucional de los derechos sociales: la reducción de las pensiones jubilares (Tema Central) - Espinosa Cueva, Karla Verónica (2021)
This article analyzes the problematic of the reduction of the retirement pensions from the critical constitutional perspective of the democratic and guarantee-based State, which includes reasonable dialogical interpretations that possess the main objective to reassure the retirees the real satisfaction of their rights within the bureaucratic and judicial apparatus, which must be specified in the practice. On the contrary, this brings a regressivity on the normative and the jurisprudential activity. For that, this investigation is developed in three different sections. The first two sections, acknowledged from the theory and the practice of social rights, social security and retirement as an object of knowledge and reflexive coherence. For that, the following methods will be usage: the hermeneutic interpretative method and hermeneutic logical method. The third performs a systematic theoretical analysis of the problem of the decreasing element of the pensions, from which can be inferred that any regressive measure of this rights requires a reasonable justification; otherwise, it is constitutionally objectionable. In conclusion, the correct functioning and operation of the institutions through progressive lectures of the norms, principles and public politics that are pro of social rights, legitimate the general well-being lecture of society.